2004
DOI: 10.1007/s00415-004-0345-z
|View full text |Cite
|
Sign up to set email alerts
|

Is the Addenbrooke?s Cognitive Examination effective to detect frontotemporal dementia?

Abstract: We evaluated the Addenbrooke's cognitive examination (ACE), a simple instrument to differentiate frontotemporal dementia (FTD) from Alzheimer's disease (AD), in our dementia patients clinic population. The Verbal-Language/Orientation-Memory (VLOM) ratio, which compares its language and memory scores, determines whether FTD or AD is more likely. The ACE was translated into French with adaptation maintaining the number of words in the name and address learning and delayed recall test, and with cultural adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 11 publications
6
41
0
5
Order By: Relevance
“…This conclusion is supported by several other studies using clinically diagnosed patients that found similar levels of discriminability when differentiating FTD from AD on the basis of tests of executive function, visuospatial abilities, and episodic memory (Elfgren et al 1994;Gregory et al 1997;Lipton et al 2005;Libon et al 2007). These differences are robust enough to be detected with relatively brief dementiascreening instruments that tap multiple cognitive functions (Mathuranath et al 2000;Bier et al 2004;Slachevsky et al 2004). …”
Section: Behavioral Variant Frontotemporal Dementiamentioning
confidence: 99%
“…This conclusion is supported by several other studies using clinically diagnosed patients that found similar levels of discriminability when differentiating FTD from AD on the basis of tests of executive function, visuospatial abilities, and episodic memory (Elfgren et al 1994;Gregory et al 1997;Lipton et al 2005;Libon et al 2007). These differences are robust enough to be detected with relatively brief dementiascreening instruments that tap multiple cognitive functions (Mathuranath et al 2000;Bier et al 2004;Slachevsky et al 2004). …”
Section: Behavioral Variant Frontotemporal Dementiamentioning
confidence: 99%
“…It assesses various cognitive domains, without requiring specialized test equipment or personnel [33]. Studies have shown that ACE can differentiate dementia subtypes, including Alzheimer’s disease, frontotemporal dementia, progressive supranuclear palsy and other atypical parkinsonian syndromes [33,34,35,36,37,38]. The ACE incorporates the MMSE, expanding on memory, language and visuospatial components, and adding a verbal fluency section [33].…”
Section: Introductionmentioning
confidence: 99%
“…Given that different cognitive deficit profiles are exhibited by patients with FTD and AD on neuropsychological test batteries, it is possible that these differences may be robust enough to be detected with relatively brief dementiascreening instruments that tap multiple cognitive functions (Bier et al, 2004;Kertesz et al, 2003a;Mathuranath et al, 2000;Slachevsky et al, 2004). An instrument that may be particularly effective in this regard is the Mattis Dementia Rating Scale (MDRS; Mattis, 1976Mattis, , 1988.…”
Section: Introductionmentioning
confidence: 99%